A5.14 Homocitrulline-Reactive Antibodies can be Generated from Synovial B-Cells from ACPA-Negative RA Patients. (25th February 2013) - Murray, Fiona; Israelsson, Lena; Steen, Johanna; Amara, Khaled; Shi, Jing; Klareskog, Lars; Trouw, Leendert; Malmström, Vivianne
Abstract : Background and Objectives: Roughly two-thirds of rheumatoid arthritis (RA) patients carry antibodies, so-called ACPA, against peptides containing citrulline, a post-translationally modified version of the amino acid (AA) arginine in their sera and/or affected joints. A recent study reported the presence of antibodies against a different kind of post-translationally modified AA, homocitrulline, also known as carbamylated proteins (CarP), where lysine residues are altered by a non-enzymatic reaction involving cyanate. The authors reported IgG antibodies recognising homocitrullinated fibrinogen in the sera of >45% of RA-patients and that 16% of ACPA-negative patients carried such anti-CarP antibodies. Furthermore, in vivo studies describe that immunisation of mice with homocitrulline-containing peptides induced erosive arthritis. Thus, homocitrulline represents an interesting immune target in the context of RA. Therefore, we aimed to assess the proportion of anti-CarP antibodies sourced from the joints of RA patients with active disease. Materials and Methods: Using a single B cell-based cloning technology to isolate the immunoglobulin (Ig) genes from joint-derived IgG+ CD19+ B-cells, we then co-transfected the paired heavy and light chains into a human cell line and produced recombinant monoclonal antibodies from each individual B cell. This approach has previously allowed for the generation of citrulline-reactive monoclonal antibodies. Here, we analysed for reactivity to carbamylated (homocitrullinated) fibrinogen and compared to its counterpart unmodified fibrinogen, by ELISA. So far, we have analysed 42 monoclonal antibodies from three ACPA-positive patients and one ACPA-negative patient, for homocitrulline reactivity. Results: Between six and eleven antibodies were tested for homocitrulline activity for the ACPA-positive patients and eleven were examined for the ACPA-negative patient. All clones screened for CarP-reactivity were negative for citrulline binding. Antibodies were made up to concentrations of 5 ug/ml down to 0.63 ug/ml in a 4-step dilution. So far, one antibody displayed reactivity to the carbamylated peptide and this antibody originated from the ACPA-negative patient. Conclusions: Although the frequency of anti-CarP reactivity amongst the 42 antibodies examined does not match that previously reported for sera, the finding of one anti-CarP antibody from an ACPA negative patient, does support the earlier finding of significant frequencies of anti-Carp antibodies amongst ACPA-negative patients. It will be of great interest to expand the investigation for anti-Carp specificities, particularly among ACPA-negative patients and determine whether these antibodies could have pathological effects in RA patients.